Faktor-faktor yang Mempengaruhi Kepatuhan Konsumen terhadap Fatwa MUI tentang Boikot Produk Israel di Kalangan Mahasiswa Muslim - Muhammad Syauqy Ridha Rabby; Hasan Zaki Mubarak; Hanathul Murohami Ashari; Dea Puspita Anggraiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Palestinian-Israeli conflict has re-emerged in recent days. This was triggered by Palestinian Hamas attacks on Israel in the southern Gaza Strip. The attacks are expected to retaliate for the various pressures and attacks that Israel has carried out against Palestine over the years. Palestinians living in the Gaza strip. It is known that they are often under pressure from Israel, such as the blockade of international aid until now, the disconnection of all networks, especially electricity and water, and very inadequate housing. This study aims to answer the research problem by focusing on Muslim students in Indonesia. This research uses a quantitative approach with the type of explanatory research, which aims to explain the influence between the independent variables on the dependent variable, namely compliance with the MUI fatwa on boycotting Israeli products. Results and discussion